2007
DOI: 10.1200/jco.2007.25.18_suppl.1024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in estrogen receptor (ER), progesterone receptor (PR) and HER2/neu status with time: Discordance rates between primary and metastatic breast pathology samples

Abstract: 1024 Background: The occurrence of changes in tumor receptor profile (ER, PR and HER-2/neu) between primary and metastatic tissue has been recognised and may have significant treatment implications. Previous reports on receptor discordance rates have tended to be from sub-studies of clinical trials. We sought to evaluate the degree of ER, PR and HER-2/neu receptor discordance in patients treated at two Canadian cancer centres. Methods: Archival data was collected on patients for whom tissue from both primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 0 publications
5
60
1
1
Order By: Relevance
“…Holdaway et al reported a significant reduction of ER expression in chest wall recurrences and visceral metastases compared with locoregional lymph node metastases, raising a possibility that tumor cells with different ER expression may be selected and adapted to grow in different anatomical sites 10. More recent studies, however, demonstrated similar rates of discordance for local recurrences and distant metastases 6, 13, 21, 22. Consistent with this, our data did not show a significant influence of metastatic site on ER concordance rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holdaway et al reported a significant reduction of ER expression in chest wall recurrences and visceral metastases compared with locoregional lymph node metastases, raising a possibility that tumor cells with different ER expression may be selected and adapted to grow in different anatomical sites 10. More recent studies, however, demonstrated similar rates of discordance for local recurrences and distant metastases 6, 13, 21, 22. Consistent with this, our data did not show a significant influence of metastatic site on ER concordance rate.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that metastatic breast carcinoma often occurs several years after the initial diagnosis of primary carcinoma, and many patients have already received a variety of systemic therapies by the time of relapse, controversy remains as to whether ER status obtained from a primary tumor can reliably guide therapeutic decisions for metastatic disease of the same patient and whether ER testing needs to be repeated for the metastatic carcinoma. In earlier studies, the reported concordance between primary and metastatic tumors varied widely from 55% to 95% 4‐15. It is notable that the majority of these studies included relatively small cohorts of patients and used the ligand‐binding assay to test ER, which is less reliable than IHC 16…”
mentioning
confidence: 99%
“…24 In BCs, the commonly used markers, ER, PR, Ki-67, or HER2, also display discordance between the primary and recurrent lesion. 25,26 Therefore, rebiopsy of the metastatic lesion to confirm the biological concordance to primary tumor is crucial upon initiation of treatment to relapsed disease. However, clinicians do not regularly perform rebiopsy to the BM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Her-2/neu overexpressive breast cancer can be treated with the humanized antibody Trastuzumab. Some studies have reported hormone-receptor status discordance rates of 10-54% between primary and recurrent breast tumors (3)(4)(5)(6)(7)(8). The mechanisms of change of hormone receptor and Her-2/neu expression have not been explicitly identified.…”
Section: To the Editormentioning
confidence: 99%